Inhibition of LINC00994 represses malignant behaviors of pancreatic cancer cells: interacting with miR-765-3p/RUNX2 axis. Issue 6 (3rd June 2019) - Zhu, Xuan; Niu, Xing; Ge, Chunlin
ABSTRACT: Pancreatic cancer exhibits one of the worst prognosis of all human cancers, and it is associated with gene dysregulation. Our microarray results first indicated long intergenic non-protein coding RNA 994 (LINC00994) as an upregulated long non-coding RNA (lncRNA) and miR-765-3p as a downregulated microRNA (miRNA) in pancreatic cancer tissues (Fold change ≥ 2 and P < 0.05; three paired samples). To investigate the role of LINC00994 in pancreatic carcinogenesis, a pair of short hairpin RNA (shRNA) was used to stably knock down the endogenous expression of LINC00994 in Panc-1 and AsPC-1 pancreatic cancer cells in vitro . We found that LINC00994 silencing inhibited the growth, migration and invasion, and promoted the G1 cell cycle arrest and apoptosis in Panc-1 and AsPC-1 cells. Furthermore, the expression of LINC00994 was negatively correlated with that of miR-765-3p in 10 pancreatic cancer specimens. Runt-related transcription factor 2 (RUNX2), a molecule that contributes to the aggressive behaviors of pancreatic cancer, was herein verified as a novel target for miR-765-3p. Like LINC00994, its expression was elevated in pancreatic cancers. Silencing of LINC00994 and RUNX2 reduced each other's expression in both Panc-1 and AsPC-1 cells. RUNX2 3ʹUTR and LINC00994 competed to bind miR-765-3p. Additionally, LINC00994-silenced cells regained their aggressive behaviors when miR-765-3p was antagonized, which was accompanied with RUNX2 re-expression. Collectively, our study reveals that LINC00994 contributes to the malignant behaviors of pancreatic cancer cells by preventing miR-765-3p from targeting RUNX2. LINC00994 can be considered as a novel therapeutic target against pancreatic cancer.